Determinants of SME tax compliance: The intervening role of tax awareness in Jakarta - Sri Rusiyati; Kurniawati Mulyanti; Instianti Elyana; Tia Ichwani (Annals of Human Resource Management Research, 2025)
Purpose: This study examines the determinants of tax compliance among Small and Medium Enterprises (SMEs) in DKI Jakarta by testing tax awareness as an intervening variable. Research Methodology: This research was conducted in DKI Jakarta, Indonesia, using a quantitative approach. Primary data were collected using a structured questionnaire administered to SME taxpayers. The conceptual model is grounded in Attribution Theory, the Theory of Planned Behavior (TPB), the Technology Acceptance Model (TAM), and Institutional Theory. This study evaluates the effects of tax knowledge, e-filing tax systems, tax authority service quality, and tax law enforcement on tax awareness and compliance. Data were analyzed using Partial Least Squares structural equation modeling (PLS-SEM) with dedicated PLS-SEM software (brand/version not specified). Results: The findings indicate that tax knowledge, the e-filing tax system, tax authority service quality, and tax law enforcement have positive and significant direct effects on tax awareness and compliance. Tax awareness also has a positive and significant effect on tax compliance and mediates the relationship between the four antecedent factors and tax compliance. Conclusions: Strengthening SME tax compliance requires improvements in knowledge, digital tax processes, service quality, and enforcement, while tax awareness functions as a key mechanism linking these factors to compliance Limitations: This study uses cross-sectional, self-reported survey data from SMEs in one province, which may limit generalizability and causal inference. Contribution: This study integrates behavioral, technological, and institutional perspectives and provides practical input for the Directorate General of Taxes to enhance voluntary awareness-based compliance among SMEs.